2020
DOI: 10.1029/2020ja027885
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Time of Arrival of Coronal Mass Ejections at Earth From Heliospheric Imaging Observations

Abstract: The time of arrival (ToA) of coronal mass ejections (CMEs) at Earth is a key parameter due to the space weather phenomena associated with the CME arrival, such as intense geomagnetic storms. Despite the incremental use of new instrumentation and the development of novel methodologies, ToA estimated errors remain above 10 h on average. Here, we investigate the prediction of the ToA of CMEs using observations from heliospheric imagers, i.e., from heliocentric distances higher than those covered by the existent c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 115 publications
2
16
0
Order By: Relevance
“…For the five events, that are also included in our study, we obtain similar results as Braga et al. (2020). Please note that we run ELEvoHI in ensemble mode in this study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For the five events, that are also included in our study, we obtain similar results as Braga et al. (2020). Please note that we run ELEvoHI in ensemble mode in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Braga et al (2020) studied 14 CMEs using the drag model and a modified version of the ELCon model, to get the CME parameters (e.g., ϕ, λ, f) based on HI observations from both STEREO spacecraft simultaneously. For the five events, that are also included in our study, we obtain similar results as Braga et al (2020). Please note that we run ELEvoHI in ensemble mode in this study.…”
Section: Discussionmentioning
confidence: 99%
“…φ, λ, f ) based on HI observations from both STEREO spacecraft simultaneously. For the five events, that are also included in our study, we obtain similar results as Braga et al (2020). Please note that we run ELEvoHI in ensemble mode in this study.…”
Section: Discussionsupporting
confidence: 66%
“…by changing the values for f (from 0.4 to 0.7). Braga et al (2020) found a value of f ∼ 0.6 for most of the CMEs in their study.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation